A longitudinal impact evaluation of a comprehensive nutrition program for reducing stunting among children aged 6–23 months in rural Malawi. Issue 1 (19th March 2021) - Hurley, Kristen M; Phuka, John; Kang, Yunhee; Ruel-Bergeron, Julie; Buckland, Audrey J; Mitra, Maithilee; Wu, Lee; Klemm, Rolf D W; West, Keith P; Christian, Parul
ABSTRACT: Background: Growth failure in sub-Saharan Africa leads to a high prevalence of child stunting starting in infancy, and is attributed to dietary inadequacy, poor hygiene, and morbidity. Objectives: To evaluate the impact of a program in Malawi providing a lipid-based nutrient supplement to infants from 6–23 months of age, accompanied by a social and behavior change communication intervention to optimize caregiver feeding and handwashing practices. Methods: This impact evaluation was a quasi-experimental, longitudinal study with 1 program and 1 comparison district. Infants were enrolled at 6–7 months of age. Anthropometry, child morbidity, and caregiver feeding and handwashing practices were assessed at enrollment and at 6, 12, and 18 month follow-ups (ages 6, 12, 18, and 24 months, respectively). Changes in the length-for-age z-score (LAZ), weight-for-length z-score (WLZ), and midupper arm circumference (MUAC) were compared using mixed-effects models. Program impacts on child stunting (LAZ < −2), wasting (WLZ < −2), morbidity, and feeding and handwashing practices were estimated using difference-in-differences. Results: We enrolled 367 infants across the program ( n = 176) and comparison ( n = 191) districts. The combined prevalences of stunting and wasting at enrollment were 42.1% and 1.4%, respectively, and did not differ by district. At enrollment, the prevalence of severe stunting (LAZ < −3) was higher in the program (15.5%) versus comparison (7.6%) district ( P = 0.02), with corresponding lower LAZ scores (−1.9 vs. −1.7, respectively; P = 0.12). Growth velocities favored program children, such that LAZ, WLZ, and MUAC measurements increased by +0.12/y ( P = 0.06), +0.12/y ( P = 0.04), and +0.24 cm/y ( P < 0.001), respectively, leading to comparable LAZ distributions across districts by 24 months of age. Program exposure was associated with 19.8 percentage point (pp) and 13.8 pp reductions in the prevalences of malaria ( P = 0.001) and fever ( P = 0.02), respectively, at the 18-month follow-up. Improvements of 20 pp ( P < 0.01) in minimum dietary diversity and minimum acceptable diet were seen in the program versus comparison district at 18 months of follow-up. Conclusions: The program improved child growth patterns, with benefits to health and diet apparent after 18 months of exposure. This trial was registered at clinicaltrials.gov as NCT02985359.